Orthodontic retention procedures: Retrospective statistical study - Mioara Decusară; Gina-Păunița Grecu; Daniela Cornea; Dorina-Cerasella Șincar (Amaltea Medical Publishing House, 2020)
Objectives. This retrospective study aimed to analyse the orthodontic retention procedures used for the stability of orthodontic treatment results and the prevention of relapse. Material and method. The study was performed over a period of 24 months, analyzing the type of procedures used for orthodontic contention for 124 patients, at age between 14 and 49 years, treated orthodontically with fixed bimaxillary apparatus, the wearing time of these devices being between 24 and 30 months. To these patiens were applied Hawley plate, vacuum-formed retainer and fixed collate retainer, depending on the dento-maxillary abnormalities, orthodontic treatment with or without extractions, dento-periodontal status and existing clinical situation, as well as the collaboration with the patients. Conclusions. To be effective, the restraint must be immediate, correctly applied or used for a long period of time.